The Political Geography of Maine’s Economic Future: Cities and Their Metro Regions - McDonnell, Joseph (Maine Policy Review, 2020)
Following a global trend that now has more than 55 percent of the world population living in cities and their metro regions, Maine’s economic and population growth are driven by our cities and the surrounding metro areas. The trend, however, will not meet Maine’s goal to attract a future workforce and reduce greenhouse gas emissions without regional solutions to housing, education, homelessness, climate adaptation, and public transportation. Meeting these challenges will require a loosening of attitudes about local control and an embracing of regional solutions to the critical issues inhibiting Maine’s economic growth. The political leadership of the state, cities, counties, and metro regions must develop new models to achieve greater density for affordable workforce housing and more public transit, including improved bus and new light-rail systems.
Keywords: Portland; Bangor; COVID-19; affordable housing; public transportation